Anomali Pernikahan dalam Tradisi Hitung Weton Perspektif Fungsionalisme-Struktural - Aris, Mustofa (Journal of Islamic Thought and Philosophy, 2023)
Marriage is a legal way of channeling one's human desires in realizing his desires while maintaining the security and safety of his religion and country. In Indonesia, especially in Java, every wedding is almost certainly accompanied by a local customary ceremony/tradition that is still valid. Among those that are still valid and used today, in Java, is the tradition of counting the weton of prospective brides and grooms. This short article will reveal the other side—anthropologically-sociologically—of the counting weton tradition and its relation to marriage which is still rooted in the minds of some Javanese Muslims. Why then does this tradition still exist today, and tend to be accepted by Javanese society in general? The author deliberately does not limit this research to certain locations, because the author's goal in this paper is the tradition of counting the weton itself. And to dissect this tradition, the author uses the Theo-Anthropological paradigm with Talcott Parsons' Functional-structural perspective.